When Onco-Immunotherapy Meets Cold Atmospheric Plasma: Implications on CAR-T Therapies - Dai, Xiaofeng; Li, Jitian; Chen, Yiming; Ostrikov, Kostya (Ken) (Frontiers in Oncology, 2022)
T cells engineered with chimeric antigen receptors (CAR) have demonstrated its widespread efficacy as a targeted immunotherapeutic modality. Yet, concerns on its specificity, efficacy and generalization prevented it from being established into a first-line approach against cancers. By reviewing challenges limiting its clinical application, ongoing efforts trying to resolve them, and opportunities that emerging oncotherapeutic modalities may bring to temper these challenges, we conclude that careful CAR design should be done to avoid the off-tumor effect, enhance the efficacy of solid tumor treatment, improve product comparability, and resolve problems such as differential efficacies of co-stimulatory molecules, cytokine storm, tumor lysis syndrome, myelosuppression and severe hepatotoxicity. As a promising solution, we propose potential synergies between CAR-T therapies and cold atmospheric plasma, an emerging onco-therapeutic strategy relying on reactive species, towards improved therapeutic efficacies and enhanced safety that deserve extensive investigations.